Performance analysis of ITO-free PEDOT:PSS/InP nanowire hybrid solar cell. (1st November 2021) - Kumar Agnihotri, Suneet; Prashant, D.V.; Samajdar, D.P.; Arefinia, Zahra
Highlights: Performance of ITO-free InP NW studied using FDTD method. Optimization of nanostructures is performed in terms of optical Jsc . Use of PEDOT:PSS instead of ITO reduces the cost of device. Influence of doping, and SRV on photovoltaic performance is investigated. PCE of ∼ 24 % is achieved with conformal coating of PEDOT:PSS over InP NW. Abstract: InP nanostructure based solar cells (SCs) offer high efficiency with reduced material requirement when compared to their planar/thin-film SCs. In order to further reduce the cost and improve the effectiveness of nanostructured SCs, a new approach by combining the organic and inorganic materials in the active layer has been developed. In this study, we have replaced the indium tin oxide (ITO) with PEDOT:PSS as the transparent conducting oxide since its sheet resistance is virtually comparable to that of ITO and exhibits almost similar performance as an electrode. Geometrical parameters such as diameter ( D ) of InP nanowire (NW) and coating thickness ( T ) of PEDOT:PSS are optimized by FDTD technique to achieve best absorption and optical current density ( J sc ). It is observed that for PEDOT:PSS/InP NWSCs with 160 nm of InP NW diameter and coating thickness of 80 nm for PEDOT:PSS, optical current density of 34.2 mA/cm 2 is achieved, which is better than the ITO/InP NWSCs. Electrical analysis of PEDOT:PSS/p-InP/n-InP NW homojunction SCs using Charge Solver Module revealed that the power conversion efficiency ( PCE ) of ∼ 24% can be attained with the proposed nanostructures through a carrier lifetime of 1 ns, surface recombination velocity ( SRV ) of 10 3 cm/s of InP NW (at n-InP and p-InP interface) and core doping of 5 × 10 18 cm −3 . We also found out that conformally coated NWs outperform fully infiltrated NW structures in terms of optical and electrical performance.